THE EFFECT OF ADVERSITY QUOTIENT AND LEARNING MOTIVATION ON SELF-REGULATED LEARNING OF GRADE XI STUDENTS IN ECONOMICS SUBJECTS AT SMAN 67 JAKARTA - Fitrianingtyas, Erissa; Nurjanah, Siti; Pratama, Aditya (International Journal of Multidisciplinary Research and Literature, 2024)
The study aims to determine the extent of the adversity quotient and the learning motivation for students’ learning, affecting their ability to self-regulate their learning in the eleventh-grade SMAN 67 Jakarta economics program. The methodology of this study is based on quantitative research. The sampling technique uses simple random sampling by selecting class XI MIPA and class XI IPS at  SMAN 67 Jakarta as representative samples, with 167 students out of 287 students. The data collection technique is a questionnaire in the form of a closed list of statements via a Google form link, and data analysis used path analysis with IBM Statistics 25. This study's results indicate a positive and significant influence effect between the adversity quotient and Self-Regulated Learning as evidenced by the t-count ≥ t-table (4.193 > 1.994). Second, there is a positive and significant effect between learning motivation on self-regulated learning as evidenced by the t-count ≥ t-table (14.013 > 1.994), and third, there is a positive and significant effect between adversity quotient on learning motivation as evidenced by the t-count ≥ - t-table (20.988> 1,994). Therefore, based on the analysis above, it can be concluded that there is a positive and significant influence between Adversity Quotient and Learning Motivation on Self-Regulated Learning